Design, synthesis and computational study of new benzofuran hybrids as dual PI3K/VEGFR2 inhibitors targeting cancer - El-Khouly, Omar A.; Henen, Morkos A.; El-Sayed, Magda A.-A.; El-Messery, Shahenda M. (Scientific reports, 2022)
Design and synthesis of a new series of benzofuran derivatives has been performed. 1 H-NMR, 13 C-NMR, elemental analysis, and IR were used to confirm the structures of the produced compounds. Hepatocellular carcinoma (HePG2), mammary gland breast cancer (MCF-7), epithelioid carcinoma cervical cancer (Hela), and human prostate cancer are used to test anticancer activity (PC3). In compared to DOX (4.17–8.87 µM), Compound 8 demonstrated the highest activity against HePG and PC3 cell lines, with an IC 50 range of 11–17 µM. Compound 8 inhibited PI3K and VEGFR-2 with IC 50 values of 2.21 and 68 nM, respectively, compared to 6.18 nM for compound LY294002 and 31.2 nM for compound sorafenib as PI3K and VEGFR-2 reference inhibitors, selectively. The molecular docking and binding affinity of the generated compounds were estimated and studied computationally utilizing molecular operating environment software as a PI3K and VEGFR-2 inhibitor (MOE). In conclusion, compound 8 exhibited significant action against hepatocellular and cervical cancer cell lines. Mechanistic study showed that it had a dual inhibitory effect against PI3K and VEGFR-2.